Green Synthesis of Gold Nanoparticles Using Moringa Oleifera Leaf Extract Bioreductor (Moringa oleifera L.) and Activity Test as Antioxidant - Indriyani, Ratna; Taufikurohmah, Titik (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Gold nanoparticles are inorganic metal materials with sizes ranging from 5-400 nm and are in the form of a suspension solution that undergoes a process of reducing particle size to nano form. This study aimed to determine the results of synthesizing gold nanoparticles (AuNPs) at a concentration of 20 ppm using a bottom-up approach with a green synthesis method characterized using a UV-Vis spectrophotometer and TEM and antioxidant activity test using DPPH. In this study, the synthesis of gold nanoparticles (AuNPs) with a concentration of 20 ppm was carried out using a bottom-up approach with the green synthesis method. The parent solution of HAuCl4 was reduced with Moringa oleifera leaf extract (Moringa oleifera L.) bioreductor, which produced burgundy-colored gold nanoparticles. The results of the characterization of gold nanoparticles using a UV-Vis spectrophotometer obtained the previous wavelength of HAuCl4 of 309 nm. After being synthesized using moringa leaf extract bioreductor (Moringa oleifera L.), the maximum wavelength was shifted to 542.80 nm, with an absorbance value of 0.213. The characterization results using TEM obtained a diverse cluster size of gold nanoparticles with an average length of 6.635 and still in the nanometer size range with the highest frequency at 4-5 nm. The antioxidant activity test of gold nanoparticles was carried out at a concentration variation of 2.5, 5, 10, and 20 ppm, obtaining the percent of free radical suppression sequentially 69, 77, 76, and 83% with an IC50 value <50, which is 0.11 ppm which indicates that the antioxidant activity of gold nanoparticles is extreme. It can be concluded that gold nanoparticles synthesized using Moringa leaf extract have the potential to be a good antioxidant.